Critical security studies : an introduction - Peoples, Columba; Vaughan-Williams, Nick (New York, NY : Routledge, 2015)
'Critical Security Studies introduces students to the sub-field through a detailed yet accessible survey of evolving approaches and key issues. This new edition contains two new chapters and has been fully revised and updated. Written in an accessible and clear manner, Critical Security Studies: - offers a comprehensive and up-to-date introduction to critical security studies - locates critical security studies within the broader context of social and political theory - evaluates fundamental theoretical positions within critical security studies in application to key issues. The book is divided into two main parts. The first part,'Approaches', surveys the newly extended and contested theoretical terrain of critical security studies: Critical Theory, Feminism and gender theory, Postcolonialism, Poststructuralism and Securitization theory. The second part,'Issues', then illustrates these various theoretical approaches against the backdrop of a diverse range of issues in contemporary security practices, from environmental, human and homeland security to border security, technology and warfare, and the War against Terrorism. This edition also includes new chapters on Constructivist theories (Part I) and health (Part II). The historical and geographical scope of the book is deliberately broad and readers are introduced to a number of key illustrative case studies. Each of the chapters in Part II concretely illustrate one or more of the approaches discussed in Part I, with clear internal referencing allowing the text to act as a holistic learning tool for students. This book is essential reading for upper-level students of Critical Security Studies, and an important resource for students of International/Global Security, Political Theory and International Relations'--
Introduction: Mapping critical security studies, and travelling without maps -- Constructivist theories -- Critical theory -- Feminist and gender approaches -- Postcolonial perspectives -- Poststructuralism and international political sociology -- Securitization theory -- Environmental security -- Health -- Homeland security and the'war against terrorism' -- Human security and development -- Migration and border security -- Technology and warfare in the information age.
Includes bibliographical references and index.
Keywords: Security, International; National security